Diagnostic value of serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP), plasma viscosity (PV) as well as fibrinogen (FIB) in acute cerebral infarction patients: Diagnostic value of serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP), plasma viscosity (PV) as well as fibrinogen (FIB) - Wang, Fei (Journal of Medical Biochemistry, 2025)
Objective: To explore the Diagnostic value of serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP),  plasma viscosity (PV) as well as fibrinogen (FIB) in patients receiving butylphthalide and sodium chloride injection in combination with atorvastatin calcium in acute cerebral infarction patients.Methods: Eighty ACI patients accepted therapy in our hospital from January 2022 to January 2024 were included to be study objects, followed by dividing into control group (CG) and study group (SG). The CG was given atorvastatin calcium tablets. On the basis of the CG, the SG accepted butylphthalide and sodium chloride injection. The clinical efficacy, neurological impairment, activity of daily living ability, hemorheological indicators, neurobiochemical indicators, and occurrence of adverse reactions in 2 groups were compared.Results: Relative to the CG, the total effective clinical effect rate in the SG presented elevation (P
Keywords: serum brain-derived neurotrophic factor (BDNF), neuronspecific enolase (NSE), glial fibrillary acidic protein (GFAP),acute cerebral infarction, butylphthalide and sodium chloride injection, atorvastatin calcium tablets, neurological impairment